Isolated Abdominal Wall Actinomycosis Associated with an Intrauterine Contraceptive Device: A Case Report and Review of the Relevant Literature - Sinan Carkman; Volkan Ozben; Haydar Durak; Kagan Karabulut; Turgut Ipek (Case Reports in Medicine)
Isolated abdominal wall actinomycosis in the presence of an intrauterine contraceptive device (IUCD) is extremely rare and only six such cases have been reported in the literature. We report a case where clinical and radiological examinations revealed a pseudotumor within the anterior abdominal wall. After being lost to follow-up, the patient presented two years later with the enlargement of the mass. The mass including the affected anterior abdominal wall was completely excised. The diagnosis of actinomycosis was established postoperatively by histopathological examination. Further questioning concerning her gynecological history revealed long-term use of the same IUCD. Surgical excision of the actinomycotic pseudotumour and removal of the IUCD followed by antibiotic therapy resulted in the full recovery of the patient.